Contribution of ER stress to tumor immunosuppressive microenvironment - Alves, Inês Sofia Moutinho (2018)
Breast cancer is the most prevalent cancer among women and also one of the oncologic pathologies that causes more deaths. In the last decades several studies have reported that solid tumors generate an immunosuppressive microenvironment. This microenvironment (acidosis, hypoxia, glucose deprivation and cytokines) is favourable to endoplasmic reticulum (ER) stress induction. ER stress is primarily a response towards the re-establishment of homeostasis; however if not resolved it usually results in cell death by apoptosis. Nevertheless, ER stress and unfolded protein response (UPR) play a paradoxical role in cancer physiopathology: the three branches of UPR, PERK, IRE1 and ATF6 actively contribute to signalling of survival and metastasis mechanisms. Recently it was reported a possible transmission of ER stress from tumor cells to immune cells, modulating the phenotype and function of recipient cells. Thus, the aim of the present work is to assess the ability and the respective mechanisms by which T-47D tumor cells transmit ER stress to THP-1 monocytes, and the consequences of this transmission. ER stress transmission was only observed when pharmacological ER stress inducers were used, such as tunicamycin, contrarily to physiological stimulation, as glucose deprivation. Additionally, it was found that tunicamycin seems to be transported within exosomes which, in turn, directly induces ER stress on monocytes. It was also observed that exosomes derived from glucose deprived T-47D cells do not transmit ER stress; however these exosomes conduct monocytes towards a particular proinflammatory profile, accompanied by the decrease of its maturation status. Overall, our results question the ER stress mechanism originally described, showing that pharmacological ER stress inducers can be transported within exosomes and directly inducing ER stress on recipient cells.